Sepiapterin alleviates impaired gastric nNOS function in spontaneous diabetic female rodents through NRF2 mRNA turnover and miRNA biogenesis pathway - Gangula, Pandu R. (Am J Physiol Gastrointest Liver Physiol, 2018)
An impaired nitrergic system and altered redox signaling contribute to gastric dysmotility in diabetics. Our earlier studies show that NF-E2-related factor 2 (NRF2) and phase II antioxidant enzymes play a vital role in gastric neuronal nitric oxide synthase (nNOS) function. This study aims to investigate whether supplementation of sepiapterin (SEP), a precursor for tetrahydrobiopterin (BH(4)) (a cofactor of NOS) via the salvage pathway, restores altered nitrergic systems and redox balance in spontaneous diabetic (DB) female rats. Twelve-week spontaneous DB and age-matched, non-DB rats, with and without dietary SEP (daily 20 mg/kg body wt for 10 days) treatment, were used in this study. Gastric antrum muscular tissues were excised to investigate the effects of SEP in nitrergic relaxation and the nNOS-nitric oxide (NO)-NRF2 pathway(s). Dietary SEP supplementation significantly (P < 0.05) reverted diabetes-induced changes in nNOS dimerization and function; nitric oxide (NO) downstream signaling molecules; HSP-90, a key regulator of nNOSα activity and dimerization; miRNA-28 that targets NRF2 messenger RNA (mRNA), and levels of microRNA (miRNA) biogenesis pathway components, such as DGCR8 (DiGeorge Syndrome Critical Region Gene 8) and TRBP (HIV1-1 transactivating response RNA-binding protein). These findings emphasize the importance of the BH(4) pathway in regulating gastric motility functions in DB animals by modulating nNOSα dimerization in association with changes in enteric NRF2 and NO downstream signaling. Our results also identify a new pathway, wherein SEP regulates NRF2 mRNA turnover by suppressing elevated miRNA-28, which could be related to alterations in miRNA biogenesis pathway components. NEW & NOTEWORTHY This study is the first to show a causal link between NF-E2-related factor 2 (NRF2) and neuronal nitric oxide synthase (nNOS) in gastric motility function. Our data demonstrate that critical regulators of the miRNA biosynthetic pathway are upregulated in the diabetic (DB) setting; these regulators were rescued by sepiapterin (SEP) treatment. Finally, we show that low dihydrofolate reductase expression may lead to impaired nNOS dimerization/function-reduced nitric oxide downstream signaling and elevate oxidative stress by suppressing the NRF2/phase II pathway through miRNA; SEP treatment restored all of the above in DB gastric muscular tissue. We suggest that tetrahydrobiopterin supplementation may be a useful therapy for patients with diabetes, as well as women with idiopathic gastroparesis.